My fair lady [videorecording (Blu-Ray)] - Hepburn, Audrey, 1929-1993; Harrison, Rex; Holloway, Stanley; Hyde-White, Wilfrid; Cooper, Gladys, 1888-1971 (Paramount, 2019)
A professor takes a wager to turn a London flower girl into someone presentable in high society.